2015
DOI: 10.4103/0976-9668.149113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relationship between salivary electrolyte levels and dental caries in children with Down syndrome

Abstract: Aim:The aim of this study was to relate the salivary electrolyte levels with dental caries in children with Down syndrome and to compare salivary electrolyte levels and dental caries of these children with their siblings.Materials and Methods:Study population consisted of 30 Down syndrome children (study group) and their 30 healthy siblings (control group). Caries status was determined by dental caries indices in deciduous and permanent dentitions. Un-stimulated saliva from both groups was collected for saliva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
7
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 19 publications
3
7
0
3
Order By: Relevance
“…A similar range of HCO 3 − concentration (1−60 mM) was reported in human saliva under normal physiological conditions [ 2 ]. Of note, the concentrations of Na + , K + and Cl − were 75.47 ± 3.57, 17.73 ± 3.70 and 18.83 ± 4.12 mM, respectively, in human saliva [ 21 ], which is a similar range as those observed in the pigs in our current study. Secretions of salivary glands are controlled by autonomic nervous system; sympathetic activates the secretion of protein-rich saliva, whereas parasympathetic activation improves the secretion of water and mucin [ 20 ].…”
supporting
confidence: 82%
“…A similar range of HCO 3 − concentration (1−60 mM) was reported in human saliva under normal physiological conditions [ 2 ]. Of note, the concentrations of Na + , K + and Cl − were 75.47 ± 3.57, 17.73 ± 3.70 and 18.83 ± 4.12 mM, respectively, in human saliva [ 21 ], which is a similar range as those observed in the pigs in our current study. Secretions of salivary glands are controlled by autonomic nervous system; sympathetic activates the secretion of protein-rich saliva, whereas parasympathetic activation improves the secretion of water and mucin [ 20 ].…”
supporting
confidence: 82%
“…In children with DS, teeth often erupts 1–2 years later than that of the normal subject. [ 8 ] Our study showed a DMFT score of 7.57 ± 5.094 in the younger age group and varied up to 13.21 ± 7.678 as observed in Group IV. It was unlike other studies that showed that DS individuals have lower values of the DMFT index.…”
Section: Discussionsupporting
confidence: 52%
“…The precise cause of the lower prevalence of dental caries in the population with DS is still unclear [ 39 , 40 ]. Although the need of treatment for dental caries is not high, these individuals must receive a dental assistance directed to the care of other needs present in this part of the population, especially periodontal disease and malocclusion, which are prevalent problems in DS.…”
Section: Discussionmentioning
confidence: 99%